Respostas
respondido por:
1
5x+(3x-4)=2(2x-3)
5x+3x-4=4x-6
5x+3x-4x=-6+4
8x-4x=-2
4x=-2
X=-2:4
X=-0,5
5x+3x-4=4x-6
5x+3x-4x=-6+4
8x-4x=-2
4x=-2
X=-2:4
X=-0,5
respondido por:
0
5x + (3x - 4) = 2.(2x - 3)
5x + 3x - 4 = 4x - 6
8x - 4 = 4x - 6
8x - 4x = -6 + 4
4x = -2
x = -2/4 (Simplificando a fração, dividindo os membros por 2)
x = -1/2
5x + 3x - 4 = 4x - 6
8x - 4 = 4x - 6
8x - 4x = -6 + 4
4x = -2
x = -2/4 (Simplificando a fração, dividindo os membros por 2)
x = -1/2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás